Accidental elemental mercury poisoning - Contreras, Carlos (2013)
Patient 19-year-old woman from Cuzco - Peru, who had ingested coffee with elemental mercury accidentally three months ago, is transferred to the Dos de Mayo National Hospital, where she is admitted to emergency room, with multiple and progressive symptoms: headache, hemoptysis, progressive dyspnea, behavior changes such as irritability and sadness, metallic taste and paresthesias in lower limbs. The predominant symptom was progressive dyspnea in medium and small efforts. Mercury levels were determined in serum (178,5 ugr/l) and urine (465 ugr/l), being elevated above the reference value for the unexposed population. She was treated with penicillamine 250 mg every 6 hours for 10 days. Additionally, she was treated with pyridoxine 100 ugr / day, because of the risk of seizures by treatment with penicillamine. The evolution was favorable, without complications and with few side effects with chelating therapy.